A sticky situation – simple method for rapid poissonian encapsulation of highly aggregation-prone microbeads in polydisperse emulsions - Hasecke, Filip; Hoyer, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2025)
Directed evolution leverages the principles of natural selection to engineer biomolecules with desired properties. Microbead-based approaches within water-in-oil emulsions have proven invaluable for high-throughput in vitro selections. However, highly aggregation-prone microbeads present significant challenges, including clustering, inconsistent distribution, and droplet instability. Here, we introduce a simple and cost-effective method for generating polydisperse emulsions with restored Poissonian distributions of highly aggregation-prone microbeads. This approach utilizes modified gel loader pipette tips, drawn out to create nozzles capable of disrupting microbead clusters during emulsification. Two widely utilized oil-surfactant formulations—mineral oil with Abil EM 90 and FluoSurf in HFE 7500 — were evaluated for emulsion preparation. Emulsions prepared using the modified nozzles exhibited exceptional stability, maintaining integrity during week-long incubations at 37°C, and reliably distributed microbeads into droplets in accordance with a Poissonian distribution despite the microbeads’ highly aggregation-prone property.